2015
DOI: 10.1158/2159-8290.cd-15-0460
|View full text |Cite
|
Sign up to set email alerts
|

PtdIns(3,4,5)P3-Dependent Activation of the mTORC2 Kinase Complex

Abstract: mTOR serves as a central regulator of cell growth and metabolism by forming two distinct complexes, mTORC1 and mTORC2. Although mechanisms of mTORC1 activation by growth factors and amino acids have been extensively studied, the upstream regulatory mechanisms leading to mTORC2 activation remain largely elusive. Here, we report that the PH domain of Sin1, an essential and unique component of mTORC2, interacts with the mTOR kinase domain to suppress mTOR activity. More importantly, PtdIns(3,4,5)P3, but not other… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
332
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 330 publications
(353 citation statements)
references
References 53 publications
6
332
1
2
Order By: Relevance
“…Note that, if this is so, simplistically, the PI (4,5)P 2 pool made by PI5P4Kα that we have invoked here must have a negative effect on mTORC2 activity. [Superficially, this might serve as the precursor for the PIP 3 pool suggested recently by Liu et al in mTORC2 regulation (24), although because this appears to be stimulatory to mTORC2, the relationship of the observations by Liu et al with our observations is unclear.] There are two proteins reported as inhibiting mTORC2, DEPTOR (25) and XPLN (26), the latter being mTORC2-specific and thus, potentially, an endoplasmic reticulum protein, and both of these proteins have the theoretical potential to bind PI(4,5)P 2 through their PDZ or PH domains, respectively; these considerations point to one way in which the negative influence of PI5P4Kα on mTORC2 activity might be mediated.…”
Section: Discussionmentioning
confidence: 47%
“…Note that, if this is so, simplistically, the PI (4,5)P 2 pool made by PI5P4Kα that we have invoked here must have a negative effect on mTORC2 activity. [Superficially, this might serve as the precursor for the PIP 3 pool suggested recently by Liu et al in mTORC2 regulation (24), although because this appears to be stimulatory to mTORC2, the relationship of the observations by Liu et al with our observations is unclear.] There are two proteins reported as inhibiting mTORC2, DEPTOR (25) and XPLN (26), the latter being mTORC2-specific and thus, potentially, an endoplasmic reticulum protein, and both of these proteins have the theoretical potential to bind PI(4,5)P 2 through their PDZ or PH domains, respectively; these considerations point to one way in which the negative influence of PI5P4Kα on mTORC2 activity might be mediated.…”
Section: Discussionmentioning
confidence: 47%
“…The accessibility of the mTOR active site is governed in part by mTORassociated proteins that form two distinct complexes: mTOR complex 1 (mTORC1) and 2 (mTORC2). These complexes differ in their composition, mode of activation and rapamycin sensitivity Liu et al, 2015). Although mTOR in both complexes interacts with DEPTOR and mLST8, the other core components are distinct between them.…”
Section: Pi3k/akt/mtor Signallingmentioning
confidence: 99%
“…Production of this phospholipid provides binding sites for protein kinase B (PKB) and phosphoinositide-dependent kinase-1 (PDK1) that migrate to the plasma membrane where PDK1 can phosphorylate PKB review in [19] . Also the protein kinase mTORC2 (mTOR in complex with rictor) is recruited to the plasma membrane to phosphorylate PKB [20] (Fig. 2).…”
Section: Insulin Signalling In Adipocytesmentioning
confidence: 99%
“…When the PH domain of PKB is bound to PIP3 a conformational change is induced, which gives PDK1 access to phosphorylate PKB. It has been suggested that also mTORC2 is recruited to the plasma membrane via the PH domain of the subunit mSIN1, thus releasing an autoinhibition of mTORC2 and thereby promoting the phosphorylation of PKB by mTORC2 [20].…”
Section: Phosphorylation Of Pkbmentioning
confidence: 99%
See 1 more Smart Citation